1997
DOI: 10.1097/00043764-199705000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Occupational Risk for Hantavirus Infection in Arizona and New Mexico

Abstract: Differentiating occupational exposure from other potential domestic or recreational exposure(s) for Sin Nombre virus (SNV) infection is an epidemiologic challenge. Interviews on work-related activities were conducted, and serum specimens were obtained from 494 workers in Arizona and New Mexico. These workers may have been exposed to rodents and rodent excreta at work, but their primary occupation did not require rodent contact (National Park Service [n = 193]; Navajo Agricultural Product Industry [n = 65], uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 9 publications
0
25
0
1
Order By: Relevance
“…Humans can acquire HPS through inhalation of aerosolized virus particles, rodent bites, or direct contact with rodent droppings or urine. Beside the general public, several groups are at higher risks of contracting the disease: mammalogists, public health workers, rodent trappers, farmers, and military personnel (Childs et al 1995;Jonsson et al 2008;Zeits et al 1997). HPS is characterized by bilateral interstitial pulmonary infiltrates, respiratory compromise usually requiring the administration of supplemental oxygen and clinical symptoms resembling those of acute respiratory distress syndrome (ARDS).…”
Section: Hantavirus Pulmonary Syndromementioning
confidence: 99%
“…Humans can acquire HPS through inhalation of aerosolized virus particles, rodent bites, or direct contact with rodent droppings or urine. Beside the general public, several groups are at higher risks of contracting the disease: mammalogists, public health workers, rodent trappers, farmers, and military personnel (Childs et al 1995;Jonsson et al 2008;Zeits et al 1997). HPS is characterized by bilateral interstitial pulmonary infiltrates, respiratory compromise usually requiring the administration of supplemental oxygen and clinical symptoms resembling those of acute respiratory distress syndrome (ARDS).…”
Section: Hantavirus Pulmonary Syndromementioning
confidence: 99%
“…The rodent transmission paradigm may be imperfect since (1) high-risk professionals (e.g., mammalogists and pest control operators) are not infected above the level of the general public (Yangihara et al 1984, Forthal et al 1987, Vitek et al 1996b, Zeitz et al 1997, (2) multiple cases of HPS are not common among cohabitants with similar rodent exposure, and (3) there is a seasonal pattern to HPS as well as a clinal pattern in prevalence in rodents (Engelthaler et al 1999). Since the exclusivity of the rodent transmission paradigm has not been fully confirmed (Dearing et al 1998), the potential for heterogenetic transmission remains.…”
Section: Introductionmentioning
confidence: 99%
“…Although some risk factors are known, for example, age, sex, and living in a rural region (4,26,27), evidence is conflicting (28,29). Some studies have shown that seropositivity is significantly higher in men than in woman, and some have reported sex as a risk factor for Hantavirus infection (7,29,31). In one retrospective study, which investigated the clinical signs of 75 patients with Hantavirus infection aged 16-82 years, the infection rate was 2.5 times higher in men than in women (10).…”
Section: Discussionmentioning
confidence: 99%